2018
DOI: 10.1177/0309324718758842
|View full text |Cite
|
Sign up to set email alerts
|

New methodology for the characterization of failure by fracture in bulk forming

Abstract: This article is focused on the formability limits by fracture obtained from standard bulk metal forming tests performed with cylindrical, tapered and flanged specimens. A total of two novel features are presented: the use of digital image correlation to determine strain paths and immersion of steel specimens in liquid nitrogen after the onset of crack formation to reveal the mode of fracture. A new methodology to determine the fracture loci in principal strain space is proposed based on the combination of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…Under these circumstances, and similar to what the authors did in bulk forming, 5 it is the intention of this article to present a new methodology to characterize formability in tube forming. The article explains how in-plane strains obtained by DIC, gauge length strains obtained from thickness measurements after cracking and force-displacement evolutions acquired from transducers can be combined to determine the strain loading paths, the strain values at the onsets of failure by necking and fracture and the critical experimental values of ductile damage in tube forming.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Under these circumstances, and similar to what the authors did in bulk forming, 5 it is the intention of this article to present a new methodology to characterize formability in tube forming. The article explains how in-plane strains obtained by DIC, gauge length strains obtained from thickness measurements after cracking and force-displacement evolutions acquired from transducers can be combined to determine the strain loading paths, the strain values at the onsets of failure by necking and fracture and the critical experimental values of ductile damage in tube forming.…”
Section: Introductionmentioning
confidence: 68%
“…4 However, recent developments by the authors showed that combination of DIC and force–displacement measurements can be successfully utilized to obtain the experimental strain loading paths up to fracture in bulk formability tests performed with cylindrical, shear, tapered and flanged specimens. 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the DIC technique has been also used in bulk metal forming, but the utilization has been limited to the determination of the stress-strain curves. Magrinho et al studied the formability limits by fracture obtained from standard bulk metal forming tests performed with cylindrical, tapered and flanged specimens in which DIC was used to determine strain JIMSE 2,2 paths and immersion of steel specimens (Magrinho et al, 2018). Except for sheet and bulk metal forming, the application of the DIC technique in tube forming has also been reported.…”
Section: Errors Affecting Dic Measurementsmentioning
confidence: 99%
“…Repeatability and consistency of the measurements was ensured by testing a minimum of ten tubes for each material type. The identification of the onset of necking in the surface strain evolutions with time was determined by means of a procedure that authors previously developed and used in bulk forming [24] and tube forming. [25] The procedure combines the surface strains and the expansion force evolutions with time to identify the strain values at the point corresponding to the drop in force, because plastic instability refers to a condition beyond which tube expansion should continue under a falling force (Figure 3b).…”
Section: Tube Expansion Tests and Formability Characterizationmentioning
confidence: 99%